Evidence for Resilience Livestock: Guide to Livestock Data Analysis in the ERA Dataset - Joshi, Namita; Steward, Peter Richard; Rosenstock, Todd Stuart (2024)
This guide provides a comprehensive overview of livestock-related data within the Evidence for Resilient Agriculture (ERA) dataset. It focuses on the exploration of data regarding animal feed nutritional composition, digestibility, and livestock outcomes. The guide outlines the methodology used for data collection, including search terms, screening criteria, and data extraction processes. It further delves into the structure and utility of the ERA data model, enabling users to explore livestock-specific studies and associated metadata.